Evaluation of the Rationality of Antihypertensive Drug Use in Hypertension Patients at Peusangan Siblah Krueng Public Health Center, Bireuen District - Adduana, Nuva; yuziani, yuziani; Novalia, Vera (Universitas Ahmad Dahlan, 2025)
Hypertension is a chronic disease with a high prevalence and a significant risk of serious complications if not properly managed. The aim of this study was to evaluate the rational use of antihypertensive drugs in hypertensive patients at Peusangan Siblah Krueng Public Health Center, Bireuen District, based on the criteria of appropriate indication, appropriate patient, appropriate drug, and appropriate dose according to JNC VIII guidelines. This was a descriptive observational study with a retrospective approach using medical records of hypertensive patients in 2023. A total of 185 patients were selected through purposive sampling based on inclusion and exclusion criteria. Data collected included patient identity, diagnosis, type of antihypertensive drugs, dosage, and administration. Rationality was evaluated using the 4T classification (appropriate indication, patient, drug, and dose) in accordance with JNC VIII guidelines. The results showed that appropriateness of indication and patient both reached 100%. Appropriateness of drug was 96.8%, with the majority of patients receiving amlodipine as the main therapy. Appropriateness of dose was 98.9%, with a small proportion of inappropriateness observed in patients with comorbid diabetes mellitus. Overall, the use of antihypertensive drugs in hypertensive patients at Peusangan Siblah Krueng Public Health Center, Bireuen District, can be categorized as rational based on the 4T criteria, although some discrepancies remain in drug selection and dosage, particularly among patients with comorbidities.